An Update on the Therapeutic Potential of Antimicrobial Peptides against Acinetobacter baumannii Infections - Karyne Rangel; Guilherme Curty Lechuga; David W. Provance; Carlos M. Morel; Salvatore G. De Simone (MDPI AG, 2023)
The rise in antibiotic-resistant strains of clinically important pathogens is a major threat to global health. The World Health Organization (WHO) has recognized the urgent need to develop alternative treatments to address the growing list of priority pathogens. Antimicrobial peptides (AMPs) rank among the suggested options with proven activity and high potential to be developed into effective drugs. Many AMPs are naturally produced by living organisms protecting the host against pathogens as a part of their innate immunity. Mechanisms associated with AMP actions include cell membrane disruption, cell wall weakening, protein synthesis inhibition, and interference in nucleic acid dynamics, inducing apoptosis and necrosis. Acinetobacter baumannii is a critical pathogen, as severe clinical implications have developed from isolates resistant to current antibiotic treatments and conventional control procedures, such as UV light, disinfectants, and drying. Here, we review the natural AMPs representing primary candidates for new anti-A. baumannii drugs in post-antibiotic-era and present computational tools to develop the next generation of AMPs with greater microbicidal activity and reduced toxicity.